Chinese Herbal Medicine for Irritable Bowel Syndrome: A Meta-Analysis and Trial Sequential Analysis of Randomized Controlled Trials - Zheng, Hui; Jin, Song; Shen, Yin-Li; Peng, Wen-Yan; Ye, Kun; Tang, Tai-Chun; Zhao, Jun; Chen, Min; Li, Zhi-Gang (Frontiers in Pharmacology, 2021)
Purpose: Chinese herbal medicine (CHM) is an important alternative and complementary therapy for the management of IBS, previous meta-analyses suggested that it is effective, but the finding is inconclusive owing to repeated significance testing. We aimed to examine the efficacy of CHM for IBS through a meta-analysis and trial sequential analysis (TSA). Methods: We searched OVID Medline, Embase, Cochrane Central Register of Controlled Trials, and Web of Science from Jan 1st 1980 to Sep 20th 2020. The primary outcome was adequate relief of global IBS symptoms. Outcome estimates Risk Ratio (RR), and required information size (RIS) was calculated for each outcome. Results: Ten trials including 2501 participants were included. Seven (70%) trials were at low risk of bias. Compared with placebo, CHM showed significantly higher proportion of adequate relief of global IBS symptom (RR, 1.76[95%CI, 1.33 to 2.33), I2=81.1%, p<0.0001]. The RIS was 1083 for the primary outcome, and the accrued information size was 1716. CHM showed significantly higher proportion of relief of abdominal pain and higher proportion of adverse events. Conclusion: CHM was effective in relieving IBS symptoms but caused higher adverse event rate than placebo. TSA analysis confirmed the findings with sufficient information size.